GeneClinics: a hybrid text/data electronic publishing model using XML applied to clinical genetic testing. - Tarczy-Hornoch P; Shannon P; Baskin P; Espeseth M; Pagon RA; Tarczy-Hornoch, P; Shannon, P; Baskin, P; Espeseth, M; Pagon, R A (Journal of the American Medical Informatics Association, 2000)
GeneClinics is an online genetic information resource consisting of descriptions of specific inherited disorders ("disease profiles") as well as information on the role of genetic testing in the diagnosis, management, and genetic counseling of patients with these inherited conditions. GeneClinics is intended to promote the use of genetic services in medical care and personal decision making by providing health care practitioners and patients with information on genetic testing for specific inherited disorders. GeneClinics is implemented as an object-oriented database containing a combination of data and semistructured text that is rendered as HTML for publishing a given "disease profile" on the Web. Content is acquired from authors via templates, converted to an XML document reflecting the underlying database schema (with tagging of embedded data), and then loaded into the database and subjected to peer review. The initial implementation of a production system and the first phase of population of the GeneClinics database content are complete. Further expansion of the content to cover more disease, significant scaling up of rate of content creation, and evaluation redesign are under way. The ultimate goal is to have an entry in GeneClinics for each entry in the GeneTests directory of medical genetics laboratories-that is, for each disease for which clinical genetic testing is available.